PENGARUH ANGGARAN KAS, PELAKSANAAN PENATAUSAHAAN BELANJA, DAN KEPATUHAN PENGELOLA KEUANGAN SKPD TERHADAP PENYERAPAN ANGGARAN BELANJA DI PEMERINTAH KOTA PADANG PANJANG - Indriani, Jennisa Dwina; Putri, Anne; Kemala, Sri; Hurnis, Delfi; Handana, Bonny (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the impact of Cash Budgeting, Budgetary Administration Implementation, and Compliance of SKPD Financial Managers on the effectiveness of Budget Expenditure Absorption in the Padang Panjang City Government. The issue of low budget absorption remains a recurring and significant concern each year. This phenomenon is evident in the disparity between actual budget absorption and the ideal projection based on quarterly, semi-annual, and year-end periods. Cash budgeting, the process of budgetary administration, and the compliance of SKPD financial managers are considered crucial factors in enhancing budget absorption at the local government level. This research is pertinent to assist SKPDs in Padang Panjang City in evaluating the challenges hindering optimal budget absorption. The study employs a quantitative method to analyze data through a descriptive approach. The data analysis technique used is Partial Least Square (PLS), with the research population comprising all SKPDs in Padang Panjang City and a sample size of 50 units. The findings reveal that Cash Budgeting and Compliance of SKPD Financial Managers have a positive and significant impact on budget expenditure absorption, while Budgetary Administration Implementation demonstrates a positive but insignificant effect.